Is partial root-zone drying more appropriate than drip irrigation to save water in China? A preliminary comparative analysis for potato cultivation - Qin, J.; Ramírez, D.; Xie, K.; Li, W.; Yactayo, W.; Jin, L.; Quiróz, R. (Springer, 2018)
China is the largest worldwide potato producer where around half of the crops is planted in the semi-arid region frequently affected by water restriction. While innovative methods are needed for water-saving irrigation methods, the use of low-cost and environmental-friendly technology must be prioritised. In this study, potato production under drip irrigation (DI, commonly adopted to save water) was compared with partial root-zone drying furrow irrigation (PRD) using the same water volume per irrigation, in both methods. Two initiation timings (early and late) were tested under shelter and field conditions, the water supplied during every irrigation being 50% of the crop water demand calculated for furrow full irrigation (FI, as control). The comparison of both methods was done through the assessment of tuber fresh-yield and estimated economic and environmental (carbon footprint and irrigation water use efficiency, WUEi) benefits. Late PRD and DI produced the highest WUEi without significant yield reduction. PRD produced 3.1% higher net benefit than DI with an estimated CO2 emission of 3659 kg ha−1 CO2 (14% lower than DI). The input-output ratio (total input costs/yield output) for PRD was 0.4, which was 10% lower than DI. The study’s results suggested that PRD, with no less than 50% of the water applied in FI per application, not only maintained yield but could also increase revenues while saving water and reducing CO2 emissions, compared to DI. Such results might help reduce the pressure on the water reserves in semi-arid potato-producing areas in China. Notwithstanding, a scaling-up of PRD technology must be tested in those regions to substantiate the findings of this preliminary study.